Student Support and Academic Performance: Experiences at Private Universities in Mexico - Canton, Erik; Blom, Andreas (2012)
Financial aid to students in tertiary education can contribute to human capital accumulation through two channels: increased enrollment and improved student performance. We pay particular attention to the latter channel, and study its quantitative importance in the context of a student support program from the Sociedad de Fomento a la Educacion Superior (Society for the Promotion of Higher Education) (SOFES) implemented at private universities in Mexico. Administrative data provided by SOFES are analyzed using a regression-discontinuity design. The advantage of the regression-discontinuity method is that it represents a natural experiment with randomly assigned treatment so that selection issues are minimized. The empirical results suggest that this financial aid package (loans and scholarships) contributes to better academic performance.